Convection heat transfer from discrete heat sources in a liquid cooled rectangular channel - BHOWMIK, H; TSO, C; TOU, K; TAN, F (2005)
Steady-state experiments are performed to study general convective heat transfer from an in-line four simulated electronic chips in a vertical rectangular channel using water as the working fluid. The experimental data covers a wide range for laminar flow under natural, mixed and forced convection conditions with Reynolds number based on channel hydraulic diameter ranging from 40 to 2220 and Reynolds number based on heat source length ranging from 50 to 2775, respectively. The heat flux ranges from 0.1 W/cm(2) to 0.6 W/cm(2). The inlet water temperature is at 24 degrees C. The effect of heat fluxes, flow rates and geometrical parameters such as chip number are investigated. The experimental results indicate that the heat transfer coefficient is strongly affected by Reynolds number and fully-developed values of heat transfer coefficient are reached before the first chip. Empirical correlations are developed for relations using Nusselt number, Reynolds number and Grashof number, based on channel hydraulic diameter. (c) 2005 Elsevier Ltd. All rights reserved.